Narrating generations: representations of generationality and genealogy in contemporary British Asian narratives - Weingarten, Jutta Karen; Justus Liebig University Giessen (My University, 2012)
The present study aims to introduce the concept of generation into literary and cultural studies. While the concept has previously been applied to literary history and genre theory, the present study breaks new ground in leaving behind the authorial biography, temporal classifications in literary periods, and the notion of family resemblances to analyse the representations of generations in contemporary migration literature. A text-immanent, work-oriented focus on how the two central aspects of generation, generationality and genealogy, are represented in narratives is this study´s point of departure. The doubled conceptuality of generation, that includes the aspects of generationality and genealogy, is based on the interrelationship of the etymological roots of the term: the Latin generatio, meaning procreation, and the Greek genos, meaning gender, genus. These two semantic levels reflect upon the different theoretical approaches to generations: Either, research on generations focuses on social generations and generationalities, meaning the formation of communities based on shared experience and the development of a generational identity; or on the succession of generations in families or other relational associations, conducting a form of genealogical research. This double conceptuality of generation invites the interdisciplinary research that characterizes generation studies. Combining generation studies and literary and cultural studies to analyse the representations of generations in contemporary British Asian narratives is the central aim of this study. As an overview over the state of generation studies shows, this very diverse and interdisciplinary field benefits from the combination of generation and literary studies in that the latter provides a methodological approach to representations of generations in narratives that is conducive to further research. In return, literary and cultural studies benefit from a generation studies´ perspective on migration literature, which offers new approaches to the interpretation of the narratives that otherwise might have been reduced to the analysis of a generation conflict between first- and second-generation immigrant characters. Narrating Generations consequently aims to explore three central research objectives. First, this study wants to explore the full potential of the concept generation by examining its versatility that can be broken down to the aspects generationalities and genealogies. Studying the functions of both aspects and highlighting the intersections as well as the correlations of both, the present study aims at a combination of generation studies and literary and cultural studies to offer new approaches to the interpretation of migration literature, which so far has received only scant attention. Second, the present thesis aims to provide a comprehensive methodological framework to analyse literary representations of generations that will inform generation studies´ methodological approaches that until now are limited to empirical research. Third, exploring the notion of generation narratives, Narrating Generations hopes to make a contribution to the discussion of genres that represent generations in migration literature by pointing out how the representation of generations influences generic attributions and how focusing on generations leads to the development of new genres. These three main objectives challenge previous usages of generation in literary studies and propose a new perspective on the field of British Asian narratives.
Generationen erzählen: Die Darstellung von Generationalität und Genealogie in zeitgenössischer britisch-asiatischer Erzählliteratur
Keywords: Generation; Generationalität; Genealogie; Erzählliteratur; generation; generationality; genealogy; narratives; ddc:820